The Classification and Extraction of Effective Knowledge in Concept Lattices Based on the Conjugate Pair of Deficient Value - Jie Wu; Yuan Ma (2011 Second International Conference on Intelligent System Design and Engineering Application, 2012)
In this paper, we define the concept of Projective Granule, Deficient Value, and Conjugate Pair, and achieve relevant formalized theorems and proofs. Then we find a Algorithm by which all Conjugated Pairs in the formal context can be obtained. The gain of the conjugate pair could classify the knowledge of concept lattice in accordance with some attributes (or objects) that users concern, and thus it has the significance in the extraction of useful knowledge.